2008
DOI: 10.1002/dev.20321
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stimulus type and early motherhood on attentional processing

Abstract: The present study evaluated the impact of stimulus type and early motherhood on attentional processing. Auditory ERPs were recorded with a modified novelty oddball paradigm both in mothers who had recently given birth and in control women who were not in the state of early motherhood. Conventional tone pips were used as standards and deviants, and an infant cry served as an experimental stimulus of novelty value. Differences were revealed in the N100 amplitudes between the study groups with higher amplitudes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Consistent with prior research (Purhonen, Kilpeläinen-Lees, et al, 2001; Purhonen et al, 2008), we found the N100 was modulated by the content of the auditory stimuli. Specifically, the largest N100 was elicited by high-distress infant cries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior research (Purhonen, Kilpeläinen-Lees, et al, 2001; Purhonen et al, 2008), we found the N100 was modulated by the content of the auditory stimuli. Specifically, the largest N100 was elicited by high-distress infant cries.…”
Section: Discussionsupporting
confidence: 91%
“…This has included ERP studies examining very early perceptual processing of infant vocalizations and facial expressions, namely the N100 and N170. With respect to infant cry perception, maternal and non-maternal samples have been exposed to infant cry and control (i.e., a word) stimuli, and the N100 elicited by these stimuli was modulated by both the nature of the stimulus (cry vs. word) and maternal status (mother vs. non-mother; (Purhonen, Kilpeläinen-Lees, et al, 2001; Purhonen, Valkonen-Korhonen, & Lehtonen, 2008)). Further, with respect to early face perception, the N170 elicited by infant faces has also showed differences by maternal status (Proverbio, Brignone, Matarazzo, Del Zotto, & Zani, 2006).…”
mentioning
confidence: 99%
“…Thus new mothers may have a heightened response to the initial detection of auditory stimuli, which is not infant specific. Taken together, these findings suggest that new mothers may have a lower perceptual threshold whereby emotional and non-emotional auditory cues elicit a greater neural response relative to non-mothers in early stimulus detection (Purhonen et al, 2008). …”
Section: Neural Response To Infant Criesmentioning
confidence: 91%
“…Converging evidence shows heightened detection and emotional response to infant auditory cues, as well as possibly increased arousal more generally to auditory stimuli when comparing parents to non-parents (Purhonen, Kilpelainen-Lees, et al, 2001; Purhonen, Paakkonen, Ypparila, Lehtonen, & Karhu, 2001; Purhonen, Valkonen-Korhonen, & Lehtonen, 2008). Purhonen, Kilpelainen-Lees, and colleagues (2001) evaluated whether the N100 differed in recent mothers and non-mothers when listening to their own infant cries (in mothers), a novel infant cry (in non-mothers), and neutral word stimuli (both groups).…”
Section: Neural Response To Infant Criesmentioning
confidence: 99%
See 1 more Smart Citation